2020
DOI: 10.1186/s40780-020-00169-5
|View full text |Cite
|
Sign up to set email alerts
|

Impact of sitagliptin combination therapy and hypoglycemia in Japanese patients with type 2 diabetes: a multi-center retrospective observational cohort study

Abstract: Background Patients with diabetes are at higher risk of developing polypharmacy because of the high frequency of comorbidities. There have been several reports on the hypoglycemic risk of the combination of hypoglycemic agents and other medications. This study aimed to investigate the hypoglycemic risk of drug-drug interaction between sitagliptin and other oral hypoglycemic agents or antihypertensive agents in Japanese patients with type 2 diabetes. Methods From January 2010 to March 2012, a total of 3247 pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
2
1
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 49 publications
0
2
1
3
Order By: Relevance
“…Hypoglycemia frequently occurs in diabetic patients undergoing pharmacotherapy and is difficult to predict[ 1 - 4 ]. In the present study, we have demonstrated that FBH also occurs in non-diabetic people, although the prevalence was very low (less than 1.0% of the total) in the general population studied, in contrast to that in diabetic patients[ 12 , 13 ]. This prevalence of FBH is not dissimilar to that of hypoglycemia (0.2%-0.5%) in non-diabetic people[ 3 , 5 ].…”
Section: Discussioncontrasting
confidence: 56%
“…Hypoglycemia frequently occurs in diabetic patients undergoing pharmacotherapy and is difficult to predict[ 1 - 4 ]. In the present study, we have demonstrated that FBH also occurs in non-diabetic people, although the prevalence was very low (less than 1.0% of the total) in the general population studied, in contrast to that in diabetic patients[ 12 , 13 ]. This prevalence of FBH is not dissimilar to that of hypoglycemia (0.2%-0.5%) in non-diabetic people[ 3 , 5 ].…”
Section: Discussioncontrasting
confidence: 56%
“…However, in the risk assessment of SGLT2 inhibitor administration prior to hip fracture, patients within 30 days of treatment initiation showed a tendency for increased risk of hip fracture. Possible factors that may increase the risk of hip fractures include falls due to hypoglycemia at the initiation of antidiabetic agents 24,25 and increased urine volume caused by SGLT2 inhibitors, 26 as well as changes in bone density associated with weight fluctuations. However, there was no significant impact observed that would increase the risk to a statistically significant level.…”
Section: Discussionmentioning
confidence: 99%
“…Yapılan çalışmalarda tip 2 DM hastalarındaki hipoglisemi sıklığı %1,6-%57,44 arasında değişkenlik göstermektedir. 1,7 Birinci basamak sağlık hizmetleri ile hastane temelli sağlık hizmetlerinin kıyaslandığı çalışmalarda ise, DM hastalarında hipoglisemi sıklığı birinci basamak sağlık hizmetlerinde %13,5-25,1 iken, hastane temelli sağlık hizmetlerinde %32,1-74,9 olarak tespit edilmektedir. 8,9 Ayrıca, yapılan çalışmalarda bizim çalışmamızla benzer şekilde, DM hastalarının hipoglisemi sıklığı birinci basamak sağlık hizmetlerinde hastane temelli sağlık hizmetlerine göre düşük saptanmıştır.…”
Section: Discussionunclassified
“…10 Yapılan bazı çalışmalarda hipoglisemi olan hastalarda DM süresi açısından fark gözlenmezken, bazı çalışmalarda DM süresi ile hipoglisemi varlığı arasında ilişki tespit edilmiştir. 7,[11][12][13][14][15][16] Yapılan çalışmalarda hem ciddi hem de hafif hipoglisemi atağı sıklığı insülin kullananlarda yüksek gözlenmiştir. 12,16,17 Bir çalışmada tip 2 DM hastalarında sadece insülin kullanımının hipoglisemi riskini 6,5 kat arttırdığı bulunmuştur.…”
Section: Discussionunclassified
See 1 more Smart Citation